Museum Experience Revisited. - Falk, John H. (John Howard), 1948- (Left Coast Press, 2012)
The first book to take a ""visitor's eye view"" of the museum visit when it was first published in 1992, The Museum Experience revolutionized the way museum professionals understand their constituents. Falk and Dierking have updated this essential reference, incorporating advances in research, theory, and practice in the museum field over the last twenty years. Written in clear, non-technical style, The Museum Experience Revisited paints a thorough picture of why people go to museums, what they do there, how they learn, and what museum practitioners can do to enhance these experiences.</D.